Pengalaman Intersubyektif Remote Audit Masa Post Covid - Risyad Alfiqho; M. Nur Abdullah Birton; M. Adrian Muluk (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to explain interactions (intersubjective) between individual auditors and between auditors and auditees in implementing remote audits from the engagement, planning, implementation and reporting stages after the COVID-19 pandemic. This research applies a qualitative approach in an interpretive paradigm and phenomenological methods. In-depth interviews were conducted with four auditors and one auditee. Using Alfred Schutz's intersubjective phenomenology to describe the experiences and meanings of each informant and combined with Interpretative Phenomenological Analysis (IPA). The research results show that after the COVID-19 pandemic, the use of hybrid methods resulted in the intensity of direct interaction between audit teams reducing reductions in the planning and implementation stages. Meanwhile, direct interaction with auditees is increasing compared to during the pandemic. The effective use of remote audits post-pandemic has implications for making audit data collection easier, auditors can focus more on examining material accounts and shorten audit time in meeting audit deadlines.